The Viability of the Stallion Spermatozoa after Centrifugation with Different Level of Seminal Plasma in Skim Milk Extender - Arifiantini, RI; Yusuf, T Laswardi; Purwantara, B (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2006)
The objective of the research was to evaluate the speed and duration of centrifugation and seminal plasma levels on the viability of stallion spermatozoa. Semen was collected from three stallions twice a week. The collected semen then evaluated macro- and microscopically. Exp I, the semen was diluted 1:1 with skim milk extender and then centrifuged at 2000 and 3000 rpm for 15 and 20 minutes each. The seminal plasma was removed, and the sperm pellet was re-diluted with skim milk extender. The extended semen then divided in two tubes, stored in 5oC and in a room temperature. The semen then was examined every 3 hours for room temperature and 12 hours for 5oC. Exp II, the semen diluted 1:1 with skim milk extender and then centrifuged at 3000 rpm for 15 minutes. The seminal plasma was removed and the pellet was re-diluted with skim milk extender consisted of 0%, 25%, 50% and 75% of the seminal plasma. The extended semen then was stored in 5oC and examined daily. Results showed that speed and duration of centrifugation had no effect on the quality of stallion semen. The liquid semen without seminal plasma showed 47.50% motile sperms and 61.00% life sperms, wich were significantly higher (P<0.05) than those with seminal plasma. It was concluded that the speed and duration of centrifugation had no effect on the semen quality and removal of seminal plasma is beneficial for stallion spermatozoa. (Animal Production 8(3): 160-167 (2006) Key Words : Centrifugation, stallion semen and seminal plasma